A Case of Pernicious Anemia with Concurrent Beta-Thalassemia Minor - Yuan F; Huang Z; Yao D; Sun J (Journal of Blood Medicine, 2024)
Fuzhen Yuan,1 Zhenhua Huang,1,2 Dingye Yao,1,2 Junsheng Sun1,2 1Department of General Practice, Longgang District Central Hospital of Shenzhen, Shenzhen, 5181116, People’s Republic of China; 2Shenzhen Clinical College of Medicine, Guangzhou University of Chinese Medicine, Shenzhen, 5181116, People’s Republic of ChinaCorrespondence: Junsheng Sun, Department of General Practice, Longgang District Central Hospital of Shenzhen, No. 6082, Longgang Avenue, Longgang District, Shenzhen, Guangdong Province, 518100, People’s Republic of China, Tel +86-15338897372, Email junshengsun@126.comAbstract: Vitamin B12 is essential for various bodily functions, and its deficiency may cause hematological manifestations. We report a case of a previously healthy 65-year-old female who was admitted to our hospital with reduced sense of taste and painful tongue. The serum level of vitamin B12 was decreased. However, her complete blood count did not show any evidence of macrocytosis, instead, her mean corpuscular volume was low. Gene sequencing indicated an β-thalassemia minor and that probably masked the megaloblastic features of vitamin B12 deficiency.Keywords: pernicious anemia, autoimmune gastritis, thalassemia, glossitis